Oxygen Behavior in High Temperature Plasma and its Applications to Hydrocarbon Fuels - Uhm, Han S.; Choi, Chang H.; Kim, Dong J.; Lee, Joo Y.; Woo, Sang G. (Journal of the Korean Physical Society, 2019)
Oxygen molecules breakdown to atoms by impact dissociation of electrons in a microwave oxygen torch. Typical atom density of oxygen in a microwave torch is a few times of 1018/cm3 produced within millisecond time scale. Dwelling time of an oxygen fluid element in a discharge tube is longer than 10 milliseconds, which is much longer than the atom production time. The oxidation coefficient of hydrocarbon fuel in oxygen atoms is usually about one million times faster than that in oxygen molecules. As an example of applications, oxygen atoms are applied to dimethyl ether, which is relatively a large molecular structure. The initial breakdown species of DME molecules in a high-temperature reaction chamber are hydrogen, carbon monoxide and methane, which is also breakdown to CO and H2 by oxygen atoms. Abundance of water may be generated in a reaction chamber of relatively low-temperature lower than Tg = 1500K, hindering an efficient production of synthetic gas. DME disintegration in a hot chamber by a microwave oxygen torch is experimentally observed. Experimental observation is somewhat agreeing with theoretical predictions.
Keywords: Dimethyl Ether; Microwave torch; Oxygen atoms; Oxygen plasma